Training evaluation: process, benefits, and issues (2014)
Training is an organized approach to positively impacting individuals' knowledge, skills, and attitudes in order to improve individual, team, and organizational effectiveness. Training gives organizations access to resources that will allow them to compete successfully in a changing environment, and to plan for and accomplish set goals. Effective training helps corrects employee and organizational deficiencies. However, poor, inappropriate, or inadequate training can be a source of frustration for everyone involved. Training typically posses a number of challenges and every training process brings with it a number of questions that managers must answer. Therefore there is need for organizations and managers to understand, plan for, and critically evaluate training. Based on the aforementioned needs, this paper examines processes, benefits, and issues in training evaluation. Among the issues discussed in the paper are the meaning of training evaluation and why training evaluation is necessary; measuring training's effectiveness and impact; Kirkpatrick's four levels of evaluation; and issues with training evaluation. The paper concludes that effective training evaluation is necessary for successful management of training programs and organizational growth and development. Therefore properly evaluating training requires managers to think through the purposes of the training, the purposes of the evaluation, the audiences for the results of the evaluation, the points or spans of points at which measurements will be taken, the time perspective to be employed, and the overall framework to be utilized.